The Role of Viral Marketing in Social Media on Brand Recognition and Brand Preference in Property Sales - Sodikun, Muhammad; Kadir, Junaidin A; Wiadi, Iyus (Jurnal Ilmu Manajemen Profitability, 2024)
Viral marketing is one of the most effective marketing strategies and important.The digital technology and social media together has increased the importance of viral marketing campaigns to increase of cost efficiency and enable them to reach an audience that was expected to quickly.This study attempts to test the influence of viral marketing strategies in the introduction of brand and brand preference by developing a framework for the effectiveness of viral marketing in the context of social media and test the relationship between some variable, the introduction of brand, and preference brand. The methodology with a structured questionnaire as a means of quantitative research or partial least square (PLS ) in data processing.By the total number of 58 respondents in the gallery property pt jababeka residence. Modeling the structural (SEM) used to test hypotheses put forward. The result showed that effective positive associated viral marketing.